Analisis Aktivitas Fisik dan Konsumsi Makanan Cepat Saji sebagai Faktor Risiko terhadap Obesitas pada Siswa Siswi SMA Negeri 1 Kendari - Asmarani Asmarani; Andi Uznul Alriansyah; Juriadi Paddo; Nina Indriyani (Health Information : Jurnal Penelitian, 2018)
Obesity is a disorder that result from excessive body fat accumulation. Etiology of obesity is not clear, but generally obesity caused by imbalance of intake and energy utilization which energy intake is more than energy utilization. Alteration of consumption pattern and low physical activity at daily life also determine body fat accumulation that cause obesity. This research aimed to analyze physical activity and fast food consumption as a risk factors toward obesity at SMA Negeri 1 Kendari. This was an observational study with case-control design. This research’s samples consist of 47 cases and 47 controls that selected use random sampling. Data was analyzed using Odds Ratio. The research’s instrument was a questionnaire for physical actovity and fast food consumption among students at age 16-18 years old. The research showed that physical activity is a risk factor for obesity (OR = 8,181; 95% CI = 3,181-21,035) and fast food consumption is a risk factor for obesity (OR = 14,578; 95% CI = 5,083-41,809). We concluded low physical activity and fast food consumption more than 3 times a week were the risk factors for obesity among students at SMA Negeri 1 Kendari.